Seasonal abundance and population dynamics of cotton whitefly (Bemisia tabaci L.) under spatio-temporal environment of South Punjab, Pakistan - Abbas, Qaisar; Hameed, Asifa; Karar, Haider; Ali, Qurban; Muhammad, Noor; Hussain, Mussurrat; Faheeem, Umair; Muhammad, Taj; Ahmad, Abrar; Shahid, Muhammad; Hameed, Abid; Iqbal, Muhammad (Journal of Pure and Applied Agriculture, 2023)
Cotton whitefly (Bemisia tabaci L.) is a serious threat to qualitative and quantitative production of cotton in Pakistan since the cultivation of Gossypium hirsutum in 1980s. Cotton is grown in the southern districts of Pakistani Punjab viz., Khanewal, Vehari, Multan, D. G. Khan, Bahawalpur and Rahim Yar Khan. However, recently, the cotton production in Faisalabad, Khanewal and other districts of upper Punjab has been declined due to lower cost benefit ratio because of excessive use of pesticides, hence farmer shifted towards sugarcane and corn. However, farmers in Multan, D. G. Khan, and Rajanpur still cultivate cotton. Data of whitefly population colonization initiation, peak abundance timings and weather relations is not available in these districts. Hence a study was designed to determine the population trends of whitefly on crop for two years at D. G. Khan, Rajanpur and Multan districts during 2019-2020 (two crop seasons). Data was statistically analyzed through ANOVA and means were compared by Tukey Honestly Significance difference test using R. Correlation and regression analysis was done to determine the impact of environmental variables on whitefly abundance. Whitefly population started in last week of June in Multan while in D. G. Khan and Rajanpur it starts in 2nd week of July. The pest populations increased gradually and reached at ETL level in last week of July in D. G. Khan, while in Multan and D. G. Khan reached at highest level in 2nd week of August. In Rajanpur the pest population reached highest level during 2nd week of September. Temperature and relative humidity showed non-significant positive correlation with whitefly. During 2019-2020, maximum temperature and minimum temperature showed negative correlation while relative humidity showed positive correlation with whitefly population. Farmers should start monitoring and management of cotton whitefly from 2nd week of August to reduce pest pressure on cotton crop.